Gliadin stimulates human monocytes to production of IL-8 and TNF-alpha through a mechanism involving NF-kappaB - Jelínková, Lenka; Tucková, Ludmila; Cinová, Jana; Flegelová, Zuzana; Tlaskalová-Hogenová, Helena (FEBS letters, 2004)
Wheat gliadin is the triggering agent in coeliac disease. In this study, we documented that proteolytic fragments of gliadin, in contrast to other food antigens, induced interleukin (IL)-8 and tumour necrosis factor-alpha (TNF-alpha) production and significantly increased interferon (IFN)-gamma-induced cytokine secretion in human monocytic line THP-1 cells. Stimulation with gliadin resulted in elevated phosphorylation of the IkappaBalpha molecule and increased NF-kappaB/DNA binding activity that was inhibited by sulfasalazine, l-1-tosylamido-2-phenylethyl chloromethyl ketone and pyrrolidine dithiocarbamate (PDTC). The activation pathway was shown to be independent of the CD14 molecule. Less mature U-937 monocytes responded to gliadin stimulation by low IL-8 secretion, TNF-alpha production was not detectable. We propose that gliadin-induced activation of monocytes/macrophages can participate in mechanisms leading to the impairment of intestinal mucosa in coeliac patients.
Keywords: Triticum; Soybean Proteins; Cell Line; Ovalbumin; Tumor Necrosis Factor-alpha; Interleukin-8; Gliadin; ovalbumin; monocyty; gliadin; Amino Acid Sequence; pšenice; proteiny ze sójových bobů; ELISA; peptidové fragmenty; kinetika; Enzyme-Linked Immunosorbent Assay; lidé; Humans; NF-kappa B; Monocytes; U937 Cells; interleukin-8; sekvence aminokyselin; buněčné linie; TNF-alfa; Peptide Fragments; Kinetics; U937 buňky